Carrier detection in Sandhoff disease. - Lowden, J A (1978)
Three new cases of Sandhoff disease are reported. One infant was the second affected child in a large family. The parents, who were cousins, were part of a large kindred from an isolated community in northern Saskatchewan. We assayed total and heat-stable hexosaminidases in 38 other members of the kindred and found two distinct cohorts. Sixteen individuals had low total and low heat-stable hexosaminidase and were diagnosed as carriers of Sandhoff disease. The values for the remainder were within normal limits. In a retrospective study of data from more than 14,000 Ashkenazi Jews, who were screened for Tay-Sachs disease, six were identified as Sandhoff carriers. Our data indicate that carrier detection requires measurement of both total and heat-stable enzyme activity.